2022
DOI: 10.1080/10717544.2022.2154411
|View full text |Cite
|
Sign up to set email alerts
|

Effect and mechanism of paclitaxel loaded on magnetic Fe 3 O 4 @mSiO 2 -NH 2 -FA nanocomposites to MCF-7 cells

Abstract: Magnetic Fe 3 O 4 nanoparticles were prepared via a simple hydrothermal method and utilized to load paclitaxel. The average particle size of Fe 3 O 4 nanoparticles was found to be 20.2 ± 3.0 nm, and the calculated saturation magnetization reached 129.38 emu/g, verifying superparamagnetism of nanomaterials. The specific surface area and pore volume were 84.756 m 2 /g and 0.265 cm 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…In another study, Ni Yan et al showed that trypsin induced apoptosis. However, this ratio was within the acceptable range 40 …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In another study, Ni Yan et al showed that trypsin induced apoptosis. However, this ratio was within the acceptable range 40 …”
Section: Discussionmentioning
confidence: 82%
“…However, this ratio was within the acceptable range. 40 c-FLIP, a master anti-apoptotic factor, was shown to inhibit apoptosis in cancer cells through its binding to Ku70 41,42 (Figure 3C). Ku70/Bax complex is an anti-apoptotic complexes and after Ku70 acetylation, this complex dissociates.…”
Section: Discussionmentioning
confidence: 99%
“…And when the calcination temperature was increased to 500 ˚C, the crystallinity improved greatly and the grain size was relatively small. The growth rate of the grains increased with the increase of the calcination temperature, and the crystallinity and grain size also increased, which in turn led to a decrease of specific surface area and a reduction of adsorption capacity [30]. Therefore, 500 ˚C was chosen as the optimum calcination temperature.…”
Section: Effects Of Preparation Factors For Mnfe 2 O 4 Nanoparticles ...mentioning
confidence: 99%
“…While, magnetic nanoparticles prepared by hydrothermal method have long cycle time and small yield. The rapid combustion method has a short preparation cycle, low cost, safe, reliable, and environmentally friendly process, it is easy to produce industrially, and it can achieve the purpose of controlling the sizes and properties of magnetic nanoparticles by changing the amount of solvent and calcination temperature [28][29][30]. And the application of adsorbents prepared by this method for the removal of elemental mercury from coal combustion flue gas has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…FA can bind to FA receptors (FR) with high affinity on the membrane of various cancer cells [23]. FR overexpresses on the cell membrane of many malignant cancers, such as lung, breast, colon cancers, and liver cancers, whereas it has limited expression on the surface of normal cells of the human body [24,25]. On the other hand, doxorubicin (Dox), a kind of anthracycline therapeutic agent, is one of the most efficient therapeutics which has been used for the treatment of various cancers (breast, leukaemia, brain, liver, etc.)…”
Section: Introductionmentioning
confidence: 99%